Pengaruh Gaya Kepemimpinan , Lingkungan Kerja, Pelatihan Terhadap Kinerja Karyawan - Sri Mulyeni; Anita Lestari; Nurul Azizah; Herlina Herlina (Jurnal Kajian Ilmiah, 2023)
The purpose of this study was to determine the impact of leadership style, work environment and training on the performance of PT. Champ Resto Indonesia, whether the three independent variabels contribute to employee performance or not. From the results of research conducted by the authors, it was found that a person’s leadership style in an organization or company can affect the performance of his subordinates. The leadership style variable has a t_table value of 4,106 > 1,680 and a significance value of 0,000 < 0,05. The work environment has an effect on employee performance t_count obtained 3,274 > 1,680 as wll as a significant valued of 0,004 < 0,05. Next the training showed that the t_count value as 4,202 > 1,680 and significantly 0,000 < 0,05 partially, each independent variable had an effect on the dependent variable. And the magnitude of the calculated F value is greater than F table 32,520 > 2,82 also a significant value of 0,000 < 0,05 so it can be concluded that leadership style, work environment and training have a positive and significant impact on employee performance.